FIGHT AGAINST OPPRESSION IN PAUL VERHOEVEN'S BLACK BOOK MOVIE (2006): A MARXIST CRITICISM - ISMAWATI, ERNA NOOR (2011)
This study is aimed to show the fighting against oppression in Black Book movie by using Marxist criticism. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the Marxist analysis . The research is descriptive qualitative research. Type of data of the study is image and text taken from two data sources: primary and secondary. The primary data source is the film and manuscript of Black Book movie that is directed by Paul Verhoeven and released in 2006. The secondary data sources are other materials taken from books, journals, and internet that is related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusion. First, based on structural analysis of each element, it is clear that in this movie the director conveys a message that no one race is superior over another. The director packs his story into an interesting plot and the audience could easily understand the message of the story because all of the elements have correlation. Second, based on the Marxist analysis, Verhoeven criticizes the oppression of one group over another, for whatever bases in society's life in Netherland.